SYSTEMATIC APPROACH TO THE CONSIDERATION OF ENGINEERING AND TECHNICAL FACILITIES IN VIEW OF THEIR FUNCTIONAL, RISK AND TERRITORIAL CHARACTERISTICS, FOCUSING ON MONITORING AND PREVENTION THROUGH GNSS TECHNOLOGIES: SYSTEMATIC APPROACH TO THE CONSIDERATION OF ENGINEERING AND TECHNICAL FACILITIES IN VIEW OF THEIR FUNCTIONAL, RISK AND TERRITORIAL CHARACTERISTICS, FOCUSING ON MONITORING AND PREVENTION THROUGH GNSS TECHNOLOGIES - Petrova, Vesela (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This report aims to propose a systematic approach to the examination of engineering facilities, taking into account their functional, risk and territorial characteristics, with a focus on the possibilities for monitoring and prevention through GNSS technologies.